The Burden of Unanticipated Fiscal Policy - Christian Scharrer; Burkhard Heer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study the impact of a government spending shock on the distribution of wealth and income between cohorts in a dynamic stochastic overlapping generations model with two types of households, a Ricardian household and a rule-of-thumb consumer. We demonstrate that an unexpected increase in government spending increases income inequality and decreases wealth inequality. In contrast to conventional wisdom that the financing of the additional expenditures by debt rather than taxes especially burdens young on behalf of the old generations, we find that a bond-financed increase in government spending rather harms the Ricardian households during both working age and retirement, while the rule-of-thumb consumers benefit at working age. The crucial element in our analysis is a wealth effect that results from the decline in the price of capital due to higher government debt.
Keywords: E62; E30; E12; 330